2023
DOI: 10.1111/aogs.14521
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the epidemiology of fear of childbirth and association with intended mode of delivery: A nationwide register‐based cohort study in Finland

Abstract: Introduction Fear of childbirth (FOC) is a common obstetrical challenge that affects the health of women. The epidemiology of FOC has not been studied in Finland for the last decade. The aim of this study was to analyze the epidemiology and risk factors for FOC and to evaluate the association between FOC and the rate of elective cesarean section (CS) as an intended mode of delivery. Material and methods Data from the National Medical Birth Register were used to evaluate the epidemiology of FOC and to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Fear of childbirth has been reported to affect the mode of delivery [21,22] . The possible reason for this is that many women are full of fear of the pain caused by childbirth, they are not con dent in their ability to handle the labor process, and they will want to escape the pain of childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of childbirth has been reported to affect the mode of delivery [21,22] . The possible reason for this is that many women are full of fear of the pain caused by childbirth, they are not con dent in their ability to handle the labor process, and they will want to escape the pain of childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…It might be due to the lack of experience and information about the childbirth process for nulliparous women [ 54 ]. However, some other studies stated that multiparous women experienced FOC with a lower level [ 13 , 55 ], in which case multiparous women usually experienced traumatic or negative childbirth previously [ 7 ]. Notably, in this study, we also found higher FOC scores in pregnant women without history of cesarean section, which is inconsistent with previous findings [ 13 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the prevalence of FOC is currently rapidly increasing, 3 studies assessing this topic are warranted. In addition, as the range of symptoms caused by FOC was recently found to be higher than thought, including lower birth rate and psychological challenges, 9,10 the studies should focus on the optimal treatment of patients with FOC, and prevent the development of FOC for women without a diagnosis FOC.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of childbirth (FOC) is a common obstetrical challenge affecting women's health 1 . In Finland, the reported prevalence of FOC has increased from 1.1% in 1997 to 9.1% in 2018 2,3 . However, in other Nordic countries, the prevalence of FOC has been observed to be much higher, rising to 10%–20% 4,5 .…”
Section: Introductionmentioning
confidence: 99%